Metabolic flexibility ensures proper neuronal network function in moderate neuroinflammation - Chausse de Freitas, Bruno; Malorny, Nikolai; Lewen, Andrea; Poschet, Gernot; Berndt, Nikolaus; Kann, Oliver (Scientific reports, 2024)
Microglia, brain-resident macrophages, can acquire distinct functional phenotypes, which are supported by differential reprogramming of cell metabolism. These adaptations include remodeling in glycolytic and mitochondrial metabolic fluxes, potentially altering energy substrate availability at the tissue level. This phenomenon may be highly relevant in the brain, where metabolism must be precisely regulated to maintain appropriate neuronal excitability and synaptic transmission. Direct evidence that microglia can impact on neuronal energy metabolism has been widely lacking, however. Combining molecular profiling, electrophysiology, oxygen microsensor recordings and mathematical modeling, we investigated microglia-mediated disturbances in brain energetics during neuroinflammation. Our results suggest that proinflammatory microglia showing enhanced nitric oxide release and decreased CX3CR1 expression transiently increase the tissue lactate/glucose ratio that depends on transcriptional reprogramming in microglia, not in neurons. In this condition, neuronal network activity such as gamma oscillations (30-70 Hz) can be fueled by increased ATP production in mitochondria, which is reflected by elevated oxygen consumption. During dysregulated inflammation, high energy demand and low glucose availability can be boundary conditions for neuronal metabolic fitness as revealed by kinetic modeling of single neuron energetics. Collectively, these findings indicate that metabolic flexibility protects neuronal network function against alterations in local substrate availability during moderate neuroinflammation.
Gesehen am 17.01.2025